Pemberdayaan Masyarakat Melalui Penerapan Agroforestri Pada Lahan Kritis Di Desa Wonosoco Kacamatan Undaan Kabupaten Kudus - Hendy Hendro HS; Shodiq Eko Ariyanto; Untung Sudjianto (Universitas Muria Kudus, 2021)
Agroforestry is a form of cultivation technique that combines annual crops with seasonal crops by paying attention to environmental sustainability. Wonosoco village which is hilly is prone to erosion and flooding. In addition, the area is equipped with cave and spring tourism objects as well as a swimming pool. The area requires an annual cropping movement to strengthen the soil which has a fairly steep slope. The method used is to provide provision / socialization in the development of agrofoerstry in the yard hilly land. In addition, training and assistance on annual crop technology were also conducted to support erosion and flood free areas and increase community income. The results of community service activities are able to increase community awareness to plant annual agroforestry models, reduce erosion, and increase community income.